2000
DOI: 10.1093/jexbot/51.347.1127
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic action of low-fluence and high-irradiance modes of response of phytochrome on germination and beta-mannanase activity in Datura ferox seeds

Abstract: Seed germination is often induced by a pulse of red light perceived by phytochrome and cancelled by a subsequent pulse of far-red light. When the pulse of red light is followed by several hours of darkness, a pulse of far-red light is no longer effective and prolonged far-red is necessary to block germination. The aim was to investigate whether the red light pulse and prolonged far-red light act on the same or different processes during germination of Datura ferox seeds. Forty-five hours after the inductive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The central role of GA metabolism in the promotion of germination by phyB has been well documented in Arabidopsis , in particular the involvement of GA3ox and GA2ox (Yamaguchi & Kamiya, 2002; Cadman et al ., 2006). GA3ox also participates in the promotion of germination by light through the LFR and VLFR in Datura ferox seeds (de Miguel et al ., 2000; Arana et al ., 2007). This study showed that another GA‐related gene, EKO, seems to be controlled by the Pfr of stable phytochromes, as no effect of phyA was detected (Figs 5a, S3).…”
Section: Discussionmentioning
confidence: 99%
“…The central role of GA metabolism in the promotion of germination by phyB has been well documented in Arabidopsis , in particular the involvement of GA3ox and GA2ox (Yamaguchi & Kamiya, 2002; Cadman et al ., 2006). GA3ox also participates in the promotion of germination by light through the LFR and VLFR in Datura ferox seeds (de Miguel et al ., 2000; Arana et al ., 2007). This study showed that another GA‐related gene, EKO, seems to be controlled by the Pfr of stable phytochromes, as no effect of phyA was detected (Figs 5a, S3).…”
Section: Discussionmentioning
confidence: 99%
“…In many species, prolonged exposure to continuous FR inhibits seed germination (Hendricks et al ; de Miguel et al ; Shichijo et al ; Górski et al ; Batlla & Benech‐Arnold ). In the ecological context, this may be important to prevent germination when under strong canopy shade, where emerging seedlings would have only very limited access to light for photosynthesis and the chance of successful completion of the life cycle would be low (Smith & Whitelam ).…”
Section: Phytochrome A‐mediated Responses and Ecological Relevance Ofmentioning
confidence: 99%
“…a-Galactosidases and b-mannosidases contribute to seed galactomannan degradation (Bewley, 1997;Feurtado et al, 2001;Nonogaki et al, 2007), and bmannosidase enzyme activity has been detected in the micropylar endosperm of tomato seeds, Datura, and coffee (de Miguel et al, 2000;Mo and Bewley, 2002;da Silva et al, 2005). In Arabidopsis seeds, At3g18080 b-mannosidase transcripts accumulate mainly in embryo and At3g57520 a-galactosidase transcripts were abundant between 3 and 24 h in whole seeds (Nakabayashi et al, 2005;Penfield et al, 2006;Preston et al, 2009).…”
Section: Mannansmentioning
confidence: 99%